Has the economic crisis revealed hidden power of Croatian trade unions? Analysis of the global economic crisis effect on the development of industrial relations in Croatia - Bagić, Dragan (2011)
The global economic crisis had particularly noticeable consequences in countries whose economic growth in the period preceding the crisis was founded on personal consumption financed dominantly by foreign loans, as was the case in the Republic of Croatia. In a situation like that, the economic crisis put strong pressure on the existing employee rights, and in turn on the entire industrial relations system. Industrial relations systems with a long tradition, due to their stable institutions, show a higher degree of resistance to effects of economic crises, whereas relatively young and instable systems, such as the ones in transition countries, are significantly more susceptible to changes. The goal of this paper is to examine the extent to which such economic shocks can affect the stability of young industrial relations systems. This paper begins with an analysis of characteristics of the industrial relations system in the Republic of Croatia established during the transition period from 1990 to the beginning of the recent global crisis. Characteristics of the Croatian industrial relations system will be analysed from a comparative perspective, comparing them with characteristics of four ideal type models: Anglo-Saxon, corporatist, Mediterranean and transitional. The paper then analyses changes noticeable since the beginning of the recent global economic crisis. These changes indicate a greater power of Croatian trade unions than the power evident in the period preceding the crisis. Such a conclusion has been particularly obtruding itself in the case of public sector unions. Stemming from that is the main research question: has the economic crisis fostered changes in the industrial relations system that could lead to a new transformation of its characteristics. The paper will be based on data collected in interviews with main actors of the industrial relations system and case studies of Croatian trade unions’ actions and reactions to consequences of the global economic crisis as well as on other sources.
Projekt MZOS
ENG